Pengaruh Brand Image Terhadap Keputusan Pembelian Handphone Samsung Android di Gerai IT Center Manado - Mandagi, Viani A. L.; Kalangi, John A. F.; Mukuan, Danny D. S. (Sam Ratulangi University, 2018)
The development of the current global era increasingly leads to tough competition especially for the company. Currently the Brand Image is important in any company where the company has its own brand image that aims to launch sales in pursuit of profit. According to Surachman (2018), the brand image of some of the brands that can be identified but cannot be pronounced, such as special symbols, design, colours, or costumer perception of a product or service represented by its brand. The purpose of this research is to find out how big the influence of Brand Image towards the purchase of a Samsung Android phone at the outlet IT Centre in Manado. The population in this study i.e. the consumer Mobile Samsung Android IT Centre outlets in Manado. The samples used this study is as much as 100 respondents, using linear regression and correlation analysis. In the calculation in this study, researchers using SPSS software version 21, which could indicate whether there is a correlation between the two variables and how much influence Brand Image against a purchasing decision. Based on the results of the study i.e. the result value of R is the relation between meaning 0.348 brand image against the decision of the buyer is low. The value R square (coefficients determinative) 0.121. That value indicates that the decision of the buyer on the outlets IT Centre in Manado was 12.1% in influence by Samsung's brand image, while the 87.9% in influence by other variables in the meticulous in this research. From the result of this research the brand has positive influents’ on purchasing decisions but the level of influence is very low, because the company must continue to increase its brand image.Keywords: Brand Image, Purchase Decision